Bortezomib Induced Hepatitis B Reactivation - Salwa Hussain; Ruby Jhaj; Samira Ahsan; Muhammad Ahsan; Robert E. Bloom; Syed-Mohammed R. Jafri (Case Reports in Medicine)
Background. It has recently been reported that hepatitis B (HBV) reactivation often occurs after the use of rituximab and stem cell transplantation in patients with lymphoma who are hepatitis B surface antigen (HBsAg) negative. However, clinical data on HBV reactivation in multiple myeloma (MM) is limited to only a few reported cases. Bortezomib and lenalidomide have remarkable activity in MM with manageable toxicity profiles, but reactivation of viral infections may emerge as a problem. We present a case of MM that developed HBV reactivation after bortezomib and lenalidomide therapy. Case Report. A 73-year-old female with a history of marginal cell lymphoma was monitored without requiring therapy. In 2009, she developed MM, presenting as a plasmacytoma requiring vertebral decompression and focal radiation. While receiving radiation she developed renal failure and was started on bortezomib and liposomal doxorubicin. After a transient response to 5 cycles, treatment was switched to lenalidomide. Preceding therapy initiation, her serology indicated resolved infection. Serial monitoring for HBV displayed seroconversion one month after change in therapy. Conclusion. Bortezomib associated late HBV reactivation appears to be a unique event that requires further confirmation and brings to discussion whether hepatitis B core positive individuals would benefit from monitoring of HBV activation while on therapy.